Pengaruh Metode Filtrasi Terhadap Peningkatan Kualitas Fisik Air Muara Sungsang, Banyuasin - Meiyerani, Jeni; Melki, Melki; Widjajanti, Hary; Rozirwan, Rozirwan; Aryawati, Riris (Journal of Tropical Marine Science, 2025)
Water quality in the form of turbidity, colour, odour, taste and suspended residue are significant issues in Sungsang Banyuasin. The filter utilizes a filtration method to remove solid particles and contaminants. The research site consists of Sungsang, Sungsang II, and Sungsang III areas. The purpose of this study was to determine the water quality in the form of colour, taste, odour, turbidity, suspended residue, and salinity, as well as the ability of the filter to overcome water quality. Filtration consists of sedimentation, filter membranes, and filter media consisting of zeolite, silica, anthracite, ferrolite, activated carbon, and bioring. Water quality measurements used organoleptic to determine odour and taste, handrefractometer to measure salinity, direct reading to measure suspended residue, and spectrophotometry to measure colour and turbidity. The breech water was odourless and tasteless, and the suspended residue value ranged from 17-19 mg/L below the quality standard of 50 mg/L. Colour and turbidity values are greater than 50 on their respective scales and salinity values range from 11-13 ppt. The filtration process successfully reduced the values of suspended residue, colour, turbidity, and salinity.